Cyber-Personality and Liking Expression: A Study From WeChat Users in China - Li, Haojian; Wang, X.T. (Frontiers in Psychology, 2021)
Clicking the like button following a post on social media has become a common means of expressing and gathering social support online. Little is known about how the liking expression is linked and regulated by personality traits and communication motives. Following a preliminary survey (n = 168) about the usage of the like function on WeChat, a Chinese social media platform, we conducted an online study (n = 183) to map big five personality traits and five communication motives to the likelihood rating of liking expression. The results showed that each user had, on average, 385 WeChat friends and spent 2.2 hours and used the liking function 1.1 times each day on WeChat. The personality trait conscientiousness was negatively related to the liking expression (β = -0.505, p < .05). In contrast, agreeableness promoted the expression of liking directly (β = 0.153, p < .05) and indirectly via two communication motives, enjoyment (a: β = 0.377, p < .01; b: β = 0.433, p < .001) and passing time (c: β = 0.578, p < .05; d: β = 0.523, p < .001). The liking expression may serve as a simple index for understanding dispositional underpinnings of social media networking.